THE INFLUENCE OF INTRINSIC AND EXTERNAL MOTIVATION ON THE PERFORMANCE OF GRAB SUKABUMI DRIVERS - Gumilang, Cahaya; Mulia Z, Faizal; Komariah, Kokom (Penerbit Lafadz Jaya, 2026)
The rapid growth of digital platform–based transportation has reshaped employment patterns in Indonesia, particularly for motorcycle ride-hailing drivers. This study aims to analyze the effect of intrinsic motivation and extrinsic motivation, both partially and simultaneously, on the performance of GrabBike drivers in Sukabumi City. A quantitative approach with descriptive and associative methods was employed. Data were collected from 95 active GrabBike drivers using a structured questionnaire with a Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results show that intrinsic motivation does not have a significant effect on driver performance, indicating that internal factors such as personal needs, expectations, independence, and optimism are insufficient to directly improve performance in platform-based work settings. In contrast, extrinsic motivation has a positive and significant effect on performance, highlighting the dominant role of external factors such as company policies, incentive systems, working conditions, supervision quality, and interpersonal relationships. Furthermore, the simultaneous test reveals that intrinsic and extrinsic motivation together significantly influence driver performance. These findings suggest that performance in the context of digital labor platforms is largely driven by organizational and system-level factors rather than individual motivation alone. Therefore, improving driver performance and sustainability requires transparent policies, fair incentive mechanisms, and supportive working conditions within platform-based partnerships such as Grab.